Family Psychological Well-Being Is Reviewed From Gender And Education Level - Dewi, Annisa Dianesti; Syahrina, Hanum Midya; Sukmakarti, Laksmy Dewi; Arti, Ayu Tri; Hapsari, Wahyu Hanan; Raihana, Permata Ashfi; Raihana, Permata Ashfi (Prosiding University Research Colloquium, 2021)
The family is the first unit related to a person’s physical and psychological development. Therefore, the psychological well-being of the family becomes one of the benchmarks for the welfare of the individual in it. The purpose of this study was to determine Kesejahteraan psikologis at the family level in terms of gender and education level in early adulthood. The method used in this research is comparative quantitative. The subjects of this study were selected by purposive sampling and revealed 122 early adults on the island of Java. This study uses a two-way Anova test to test the hypothesis. The results obtained are: 1) there is no difference in the Kesejahteraan psikologis chosen by the family in terms of gender and early adult education level with p=0.372; 2) there are differences in the Kesejahteraan psikologis of families in terms of gender with a significance value of 0.046 and; 3) there is no difference in family Kesejahteraan psikologis in terms of education level with a significance of 0.246.